Construction and Classification of Symmetry-Protected Topological Phases in Interacting Fermion Systems - Qing-Rui Wang (American Physical Society, 2020)
The classification and lattice model construction of symmetry-protected topological (SPT) phases in interacting fermion systems are very interesting but challenging. In this paper, we give a systematic fixed-point wave function construction of fermionic SPT (FSPT) states for generic fermionic symmetry group G_{f}=Z_{2}^{f}×_{ω_{2}}G_{b} which is a central extension of bosonic symmetry group G_{b} (may contain time-reversal symmetry) by the fermion parity symmetry group Z_{2}^{f}={1,P_{f}}. Our construction is based on the concept of an equivalence class of finite-depth fermionic symmetric local unitary transformations and decorating symmetry domain wall picture, subjected to certain obstructions. We also discuss the systematical construction and classification of boundary anomalous SPT states which leads to a trivialization of the corresponding bulk FSPT states. Thus, we conjecture that the obstruction-free and trivialization-free constructions naturally lead to a classification of FSPT phases. Each fixed-point wave function admits an exactly solvable commuting-projector Hamiltonian. We believe that our classification scheme can be generalized to point and space group symmetry as well as continuum Lie group symmetry.